COMPARISON OF WIDAL TEST AND BLOOD CULTURE FOR DIAGNOSIS OF TYPHOID FEVER: CORRELATION WITH ANTIBIOTIC SUSCEPTIBILITY PATTERNS OF SALMONELLA TYPHI (Journal of Medical & Health Sciences Review, 2025)
Typhoid fever is a systemic infection caused by Salmonella enterica serovar Typhi, a Gram-negative bacillus predominantly transmitted through contaminated food and water. It remains a significant public health concern in low- and middle-income countries due to poor sanitation and limited access to reliable diagnostics. Early and accurate diagnosis, along with effective antibiotic treatment, is crucial for controlling morbidity and mortality. This study aimed to evaluate the diagnostic accuracy of the Widal agglutination test in comparison with blood culture for the diagnosis of typhoid fever, and to assess the antibiotic susceptibility patterns of Salmonella isolates to guide effective treatment strategies. A total of 150 patients with clinically suspected typhoid fever were enrolled from various healthcare facilities in Abbottabad, Pakistan. Patients presented with common symptoms including prolonged fever, abdominal pain, rash, headache, weakness, loss of appetite, and constipation. Widal test was performed using standard agglutination methods, with titers 1:80 (anti-TO) and ≥1:160 (anti-TH) considered positive. Blood cultures were carried out to isolate Salmonella Typhi and Paratyphi. Antibiotic susceptibility testing of isolates was performed using the Kirby-Bauer disk diffusion method. Out of 150 samples, 90% tested positive by Widal test, while only 42% yielded positive results in blood cultures. Antibiotic susceptibility profiles revealed resistance to Azithromycin (33%), Ciprofloxacin (47%), and Moxifloxacin (54%). In contrast, high sensitivity was observed to Meropenem (98%) and Imipenem (96%). The study concluded that widal test showed limited sensitivity and specificity, with a high rate of false positives compared to blood culture, which remains the gold standard for typhoid diagnosis. The study also highlights levels of resistance to commonly used antibiotics, underlining the importance of culture-based diagnosis and antibiotic stewardship in typhoid fever management.